Integrated methylome and transcriptome analysis unravel the cold tolerance mechanism in winter rapeseed(Brassica napus L.) - Zheng, Guoqiang; Dong, Xiaoyun; Wei, Jiaping; Liu, Zigang; Aslam, Ali; Cui, JunMei; Li, Hui; Wang, Ying; Tian, Haiyan; Cao, Xiaodong (BMC plant biology, 2022)
Cytosine methylation, the main type of DNA methylation, regulates gene expression in plant response to environmental stress. The winter rapeseed has high economic and ecological value in China's Northwest, but the DNA methylation pattern of winter rapeseed during freezing stress remains unclear. This study integrated the methylome and transcriptome to explore the genome-scale DNA methylation pattern and its regulated pathway of winter rapeseed, using freezing-sensitive (NF) and freezing-resistant (NS) cultivars.The average methylation level decreased under freezing stress, and the decline in NF was stronger than NS after freezing stress. The CG methylation level was the highest among the three contexts of CG, CHG, and CHH. At the same time, the CHH proportion was high, and the methylation levels were highest 2 kb up/downstream, followed by the intron region. The C sub-genomes methylation level was higher than the A sub-genomes. The methylation levels of chloroplast and mitochondrial DNA were much lower than the B. napus nuclear DNA, the SINE methylation level was highest among four types of transposable elements (TEs), and the preferred sequence of DNA methylation did not change after freezing stress. A total of 1732 differentially expressed genes associated with differentially methylated genes (DMEGs) were identified in two cultivars under 12 h and 24 h in three contexts by combining whole-genome bisulfite sequencing( and RNA-Seq data. Function enrichment analysis showed that most DMEGs participated in linoleic acid metabolism, alpha-linolenic acid metabolism, carbon fixation in photosynthetic organisms, flavonoid biosynthesis, and plant hormone signal transduction pathways. Meanwhile, some DMEGs encode core transcription factors in plant response to stress. Based on the findings of DNA methylation, the freezing tolerance of winter rapeseed is achieved by enhanced signal transduction, lower lipid peroxidation, stronger cell stability, increased osmolytes, and greater reactive oxygen species (ROS) scavenging. These results provide novel insights into better knowledge of the methylation regulation of tolerance mechanism in winter rapeseed under freezing stress.